Health Plans and Selection: Formal Risk Adjustment vs. Market Design and Contracts - Richard G. Frank; Meredith B. Rosenthal (SAGE Publishing, 2001)
In this paper, we explore the demand for risk adjustment by health plans that contract with private employers by considering the conditions under which plans might value risk adjustment. Three factors reduce the value of risk adjustment from the plans' point of view. First, only a relatively small segment of privately insured Americans face a choice of competing health plans. Second, health plans share much of their insurance risk with payers, providers, and reinsurers. Third, de facto experience rating that occurs during the premium negotiation process and management of coverage appear to substitute for risk adjustment. While the current environment has not generated much demand for risk adjustment, we reflect on its future potential.